PERUBAHAN MAKNA KATA DALAM BAHASA INDONESIA PADA KOLOM KOMENTAR YOUTUBE: RUANG GURU ACADEMY OF CHAMPIONS (AOC) EPS 2 - Nisa Fitria -; Rika Ningsih (Jurnal Lazuardi, 2026)
This research is motivated by the changes in meaning that occur in the digital space. As time goes by and social and cultural developments have created new meanings in the digital space. This triggering various changes in meaning in the comment column of the Ruang Guru Academy of Champions episode 2 YouTube. The problem in this study is how the form of change in meaning in the comment column of the Ruang Guru Academy of Champions episode 2 YouTube and what factors cause changes in meaning. This study aims to explore and elaborate on the form of change in meaning in the comment column of the Ruang Guru Academy of Champions episode 2 YouTube. The approach used in this study is a qualitative approach with the content analysis method. The data in this study are the main comments that contain changes in meaning. The data source in this study is the Ruang Guru Academy of Champions Episode 2 YouTube. Data collection techniques in this study are documentation techniques, reading techniques, note-taking techniques. Data analysis techniques in this study are coding, classification, analyzing and finding relationships and compiling a draft report. The results of this study found 87 changes in meaning, changes in meaning expanded 51 data, narrowed 3 data, total changes 32 data and roughing 1 data. The conclusion of this study is that the most dominant changes in meaning extend, amounting to 51 data points, and one change in meaning, namely refinement, was not found. The most dominant factor causing changes in meaning is social development, with several other factors missing. This suggests that social media users prefer to use vocabulary that can describe various situations.